1967
DOI: 10.1097/00006842-196705000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Review of Consultation Psychiatry and Psychosomatic Medicine

Abstract: Studies of prevalence of psychiatric morbidity in the nonpsychiatric areas of general hospitals as well as of frequency and patterns of referrals for psychiatric consultation are critically reviewed. Commoner psychiatric diagnostic and management problems encountered on the medical and surgical wards are classified and discussed. The importance of these problems for psychiatric and psychosomatic theory, as well as their practical implications for training and research, are pointed out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
3

Year Published

1969
1969
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(18 citation statements)
references
References 30 publications
1
14
0
3
Order By: Relevance
“…It not only includes diagnostic interview and assessment of the patient but also includes a psychodynamic evaluation of the patient's personality and reaction to illness. [3] The crisis-oriented approach involves a rapid assessment of patient's problem and coping styles and immediate therapeutic intervention to address the problem. [18] In the consultee-oriented approach the motive of the consultee and his related difficulties and expectations are the major focus.…”
Section: Consultation Liaison Models World Wide Vis-a-vis Indiamentioning
confidence: 99%
“…It not only includes diagnostic interview and assessment of the patient but also includes a psychodynamic evaluation of the patient's personality and reaction to illness. [3] The crisis-oriented approach involves a rapid assessment of patient's problem and coping styles and immediate therapeutic intervention to address the problem. [18] In the consultee-oriented approach the motive of the consultee and his related difficulties and expectations are the major focus.…”
Section: Consultation Liaison Models World Wide Vis-a-vis Indiamentioning
confidence: 99%
“…His writings influenced generations of psychosomatic researchers. I remember reading his review of consultation psychiatry and psychosomatic medicine [1, 2, 3]in the early seventies. I was still in medical school and was looking for articles in the journal Psychosomatic Medicine .…”
Section: Introductionmentioning
confidence: 99%
“…That material did not appeal much. By chance (but a Conradian chance), I started reading Lipowski’s articles [1, 2, 3]. My enthusiasm grew as long as the reading went on.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipowsky (1967) has reviewed the earlier studies in this area and has concluded that 50-80% of medical outpatients and 30-60% of medical inpatients had psychiatric problems. Recent studies conducted in outpatient and inpatient settings in India have shown that one third to a half of general medical patients had a recognisable psychiatric disorder (Murthy et cal.…”
mentioning
confidence: 99%